DILEMA TATA KELOLA DAN KONFLIK SPASIAL: PEMANFAATAN RUANG KAWASAN SEMPADAN DANAU PRIORITAS NASIONAL SINGKARAK - Suharizal, Suharizal; Dasrizal, Dasrizal; Juita, Erna (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2026)
Despite its designation as a National Priority Lake, Lake Singkarak faces severe environmental and institutional challenges due to unmanaged land-use intensification in its buffer zone. This study analyzes spatial land-use dynamics within the Lake Singkarak buffer zone and evaluates the governance implications of its national priority status across Solok and Tanah Datar Regencies. Employing a mixed-methods approach, GIS spatial techniques—including buffering, overlay analysis, and building digitization—were integrated with qualitative intergovernmental interviews. Spatial findings reveal significant encroachment, with 792 structures occupying the core buffer zone (<50 m) and higher development intensity in Tanah Datar Regency (160.40 ha non-residential vs. 86.66 ha residential land). Institutionally, the national priority mandate lacks effective cross-level coordination, resulting in overlapping authorities, weak land-use control, and fragmented policy enforcement. Consequently, integrating high-resolution spatial monitoring into multi-level governance frameworks is essential to align national conservation mandates with local spatial enforcement.